RancangBangunSistemInformasiPemanggilan Vendor Secondary Level MaintancePadaPT.Advantage SCM Semarang (Information Technology and Telematics, 2015)
Abstract - In a further development is found in the most effective and efficient way to conduct transactions by using the " money " . But in its development, the use of money to experience certain obstacles , carrying large amounts of cash risks that arise and must be addressed is the risk of loss , forgery or robbery exposed . Therefore, many people choose to save their money in the bank is then taken immediately when necessary through ATM . This system design goal is to create , design and produce Dialing Information System application vendor ATM machine on PT.Advantage SCM Semarang , as well as to facilitate the calling process .Data collection method used is the field of study that includes interviews or question and answer directly to systematically with the Branch Manager and employees PT.Advantage SCM Semarang . Keywords: calling system vendor , ATM machines , Prototyping Method , PHP , MYSQL